All roads lead to abolition? Debates about prostitution and sex work through the lens of unacceptable work. (2nd January 2021) - Tyler, Meagan
ABSTRACT: The notion of unacceptable work has formed, in part, as a counterweight to the push for decent or better forms of work. That is, naming and understanding the functioning of unacceptable work helps 'promote respect for rights at work by eliminating egregious labour practices'. There are important insights around unacceptable work to be gained from feminist debates on the sex industry. Engaging with these debates through the prism of unacceptable work can illuminate the way in which systems of prostitution can function simultaneously as forms of labour and as forms of exploitation and violence against women. If prostitution/sex work meets many of the criteria available for understanding unacceptable forms of work, then the question of abolition can be raised from a labour rights perspective. Following this logic, it is also possible to view the Equality/Nordic Model of asymmetric decriminalisation of the sex industry (where prostituted persons are decriminalised, but brothel owning and the purchase of sexual access are criminalised) as a form of innovative policy to address unacceptable work, and promote decent work.